Analisis Perbedaan Kemampuan Berpikir Tingkat Tinggi Peserta Didik menggunakan Problem Based Learning dan Contextual Teaching and Learning dalam Pembelajaran PAI - Fatimah, Siti; Ngabdurrohman, Ngabdurrohman; Devi, Sastiyagustin Eka; Kamilah, Zaeni (Prodi Pendidikan Agama Islam IAINU Kebumen, 2022)
This study aims to determine the differences in students' higher-order thinking skills using the PBL and CTL models in Islamic education learning. This research is a quasi-experimental research with a Posttest-Only Control Design. The population in this study were students of class X at SMA Negeri 1 Pejagoan, Kebumen Regency. The sampling technique was carried out using a purposive sampling technique so that the samples in this study were students in classes X MIPA 5 and X IPS 2. Data collection techniques were carried out with tests and non-tests. The test is structured by following the indicators of higher-order thinking skills according to the Revised Bloom's Taxonomy. While the non-test technique consists of interview and observation techniques. The data analysis technique used the t-test to determine the differences between the PBL and CTL models on the students' higher-order thinking skills. T-test calculations were carried out with the help of SPSS software. The results of the analysis show that there are differences in students' higher-order thinking skills through PBL and CTL models in Islamic education learning. This is based on a statistical test through the Independent Samples Test which produces a p-value of 0.000 < 0.005. In addition to influencing higher-order thinking skills, PBL and CTL models can develop social skills and participation, and self-confidence of students.